The relationship between workload, role conflict and work-life balance among support staff at Jabatan Kerja Raya Kuching, Sarawak / Muhammad Firdaus Amir … [et.al.]. - Amir, Muhammad Firdaus; Halizal, Nur Husnina; Stephen Lamkop, Priscilla Jara; Shahni, Zaimah (2019)
Work-life balance is also known as work-family balance, and it is defined as satisfaction and good functioning at work and home, with a minimum of role conflict. (Kim, 2014; Clark, 2000, p.751). Several empirical studies have shown that the experience of work-life balance is positively related to employees’ performance and organizational performance as well. (Kim et al. 2014; Harrington & Ladge, 2009; Parkes & Langford, 2008). According to this study, which is conducted in Korea to identify the relationship between work-life balance and employees’ performance. Employees are working in small to medium-sized enterprises experienced work- life conflicts more than those in conglomerates since they did not have family-friendly supports from their management. Besides, social situations and lack of organizational support may hinder employees’ work-life balance. It is essential that organizations understand that when employees perceive the increased organizational support for their work-life balance, the employees’ affective commitment can be increased (Kim et al.,2014; Wang, 2010; Aube, 2007).